2009
DOI: 10.1159/000262304
|View full text |Cite
|
Sign up to set email alerts
|

Nebivolol Improves Renal Function in Patients Who Underwent Angioplasty due to Renal Artery Stenosis: A Pilot Study

Abstract: Renal artery stenosis (RAS) is a progressive disease and may lead to chronic kidney disease by deterioration of renal functions. Endothelial dysfunction is an important causative factor for kidney damage after RAS revascularization. Nebivolol, a new generation beta blocker induces endothelium-related arterial relaxation by nitric oxide (NO) and may improve endothelial dysfunction. This pilot study tested the effect of nebivolol on the glomerular filtration rate (GFR) in a series of 33 patients with severe RAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 34 publications
(21 reference statements)
1
9
0
2
Order By: Relevance
“…CIN is the third leading cause of hospital-acquired acute renal failure (7). In a previous study, nebivolol has improved renal function in patients who underwent angioplasty due to renal artery stenosis (8). An experimental study in rats has also shown preventive effect of nebivolol on contrast-induced nephropathy previously (9).…”
Section: Introductionmentioning
confidence: 98%
“…CIN is the third leading cause of hospital-acquired acute renal failure (7). In a previous study, nebivolol has improved renal function in patients who underwent angioplasty due to renal artery stenosis (8). An experimental study in rats has also shown preventive effect of nebivolol on contrast-induced nephropathy previously (9).…”
Section: Introductionmentioning
confidence: 98%
“…20 In a pilot study of 33 patients with severe renal artery stenosis who underwent revascularization, nebivolol ( n =17) significantly increased estimated glomerular filtration rate and decreased proteinuria as compared with the control group. 30 Nebivolol was also found to be effective in nephrotoxicity induced by contrast media. 31 In patients pre-treated with nebivolol before coronary angiography and ventriculography, it was found that nebivolol did not increase serum creatinine.…”
Section: Oxidative Damage To the Kidney: A Role For Nebivololmentioning
confidence: 99%
“…По данным, полученным в небольшом исследо-вании, включавшем 33 пациента с реноваскулярной АГ, назначение небиволола в течение 6 месяцев по-сле операции реваскуляризации почечных артерий не влияет на выделение нитритов/нитратов с мо-чой по сравнению с контрольной группой больных, но способствует достоверному снижению протеи-нурии и повышает уровень СКФ с исходных 44,8 до 50,6 мл/мин/1,73 м 2 [13].…”
Section: клиническая эффективность небиволола у больных хронической бunclassified
“…Оба пре-парата оказывают выраженный антиоксидантный эффект и защищают почки от повреждения в экс-периментах на крысах с различными моделями гипертонической и диабетической нефропатии. Ряд данных свидетельствует о том, что небиволол и в большей степени карведилол могут препятство-вать потере альбуминов с мочой у больных гипер-тонической и диабетической нефропатиями [8,13,14,23], однако их способность замедлять прогрес-сирование ХБП у таких пациентов нуждается в кли-ническом подтверждении.…”
Section: заключениеunclassified